Fine Arts Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Later Old Bagley Hall and the Architecture Hall on the UW campus. This photograph was taken by one of the many amateur photographers allowed to photograph the grounds, buildings and exhibits of the Alaska-Yukon-Pacific-Exposition. By purchasing a day pass, an amateur photographer with a camera smaller then 6" x 8" was allowed to take unlimited pictures inside the exposition. Handwritten on verso: Meany Auditorium. PH Coll 369.4 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number